High-throughput optical action potential recordings in hiPSC-derived cardiomyocytes with a genetically encoded voltage indicator in the AAVS1 locus - Zhang, Fangfang; Meier, Anna B.; Poch, Christine M.; Tian, Qinghai; Engelhardt, Stefan; Sinnecker, Daniel; Lipp, Peter; Laugwitz, Karl-Ludwig; Moretti, Alessandra; Dorn, Tatjana (Frontiers in Cell and Developmental Biology, 2022)
Cardiomyocytes (CMs) derived from human induced pluripotent stem cells (hiPSCs) represent an excellent in vitro model in cardiovascular research. Changes in their action potential (AP) dynamics convey information that is essential for disease modeling, drug screening and toxicity evaluation. High-throughput optical AP recordings utilizing intramolecular Förster resonance energy transfer (FRET) of the voltage-sensitive fluorescent protein (VSFP) have emerged as a substitute or complement to the resource-intensive patch clamp technique. Here, we functionally validated our recently generated voltage indicator hiPSC lines stably expressing CAG-promoter-driven VSFP in the AAVS1 safe harbor locus. By combining subtype-specific cardiomyocyte differentiation protocols, we established optical AP recordings in ventricular, atrial, and nodal CMs in 2D monolayers using fluorescence microscopy. Moreover, we achieved high-throughput optical AP measurements in single hiPSC-derived CMs in a 3D context. Overall, this system greatly expands the spectrum of possibilities for high-throughput, non-invasive and long-term AP analyses in cardiovascular research and drug discovery.